Gain-enhanced feedforward path compensation technique for pole–zero cancellation at heavy capacitive loads - Chan, Pak Kwong (2009)
An improved frequency compensation technique is presented in this paper. It is based on a cascade of a voltage amplifier and a transconductor to form a composite gain-enhanced feedforward stage in a two-stage amplifier so as to broaden the gain bandwidth via low-frequency pole–zero cancellation at heavy capacitive loads, but yet without increasing substantial power consumption. The technique has been confirmed by the experimental results. An operational amplifier has been designed to drive a capacitive load of 300 pF. The amplifier exhibits a dc gain of 87 dB, a gain bandwidth of 10.4 MHz at 63.7° phase margin, an average slew rate of 3.5V/µs, a compensation capacitor of only 6 pF while consuming 2.45 mW at a 3-V supply in a standard 0.6- µm CMOS